2022
DOI: 10.1002/joc.7961
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the double easterly jets over the tropical western Pacific and their effects on tropical cyclone genesis

Abstract: Different from other upper-tropospheric jet stream that owns the single jet axis, the tropical easterly jet (TEJ) generally splits into two branches over the tropical western Pacific where the TEJ inflows from June to September, with the north branch locating near 20 N and the south branch appearing near the equator. However, how these double easterly jets change from year to year and whether they have effects on the tropical cyclones (TCs) over the tropical western Pacific are still unknown. Observational evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Most of the previous research focused on the variability of the TEJ's intensity from the intraseasonal and interannual time scales to the long-term trend (Chen and Yen 1991, Sathiyamoorthy 2005, Sathiyamoorthy et al 2007, Roja Raman et al 2009, Sreekala et al 2014, Sharma et al 2024, which can be attributed mainly to the tropical sea surface temperature (SST) anomalies and the latent heat released by the tropical convection through the modulation on the tropical divergent circulation and the meridional temperature gradient (MTG) (Ramesh et al 1996, Pattanaik and Satyan 2000, Sathiyamoorthy et al 2007, Abish et al 2013, Nithya et al 2017, Huang et al 2019, 2021. It has been well demonstrated that the change in the TEJ's intensity plays an important role in summer monsoon rainfalls in the Afro-Asian region (Hulme and Tosdevin 1989, Nicholson 2008, Fontaine et al 2011, Rai and Dimri 2017, Lemburg et al 2019, tropical cyclone activities in the North IO and western North Pacific (Rao et al 2004, 2008, Zhan et al 2022a, 2022b, the atmospheric wave and disturbance (Sasi et al 2000, Ramkumar et al 2010 as well as the northward propagation of the boreal summer intraseasonal oscillation (Jiang et al 2004, Drbohlav andWang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research focused on the variability of the TEJ's intensity from the intraseasonal and interannual time scales to the long-term trend (Chen and Yen 1991, Sathiyamoorthy 2005, Sathiyamoorthy et al 2007, Roja Raman et al 2009, Sreekala et al 2014, Sharma et al 2024, which can be attributed mainly to the tropical sea surface temperature (SST) anomalies and the latent heat released by the tropical convection through the modulation on the tropical divergent circulation and the meridional temperature gradient (MTG) (Ramesh et al 1996, Pattanaik and Satyan 2000, Sathiyamoorthy et al 2007, Abish et al 2013, Nithya et al 2017, Huang et al 2019, 2021. It has been well demonstrated that the change in the TEJ's intensity plays an important role in summer monsoon rainfalls in the Afro-Asian region (Hulme and Tosdevin 1989, Nicholson 2008, Fontaine et al 2011, Rai and Dimri 2017, Lemburg et al 2019, tropical cyclone activities in the North IO and western North Pacific (Rao et al 2004, 2008, Zhan et al 2022a, 2022b, the atmospheric wave and disturbance (Sasi et al 2000, Ramkumar et al 2010 as well as the northward propagation of the boreal summer intraseasonal oscillation (Jiang et al 2004, Drbohlav andWang 2005).…”
Section: Introductionmentioning
confidence: 99%